LET’S PROPEL USM TOGETHER TO GREATER HEIGHTS… USM STYLE - VC - MPRC, Pusat Media & Perhubungan Awam (2017)
USM, PENANG,18 February 2017 Universiti Sains Malaysia (USM) aspires to propel its name with its uniqueness and in its own mould, and to avoid relying on fate (or by chance) in implementing all of its plans.